Why should we investigate secondary school teacher beliefs and teacher perceptions of English language teaching? - Hung, Nguyen Viet (VNU Journal of Foreign Studies; Vol 27 No 2, 2011)
Abstract. The aim of this paper is to make an argumentation on why researchers should start from seeking teacher beliefs and teacher perceptions related to the teaching career. It is organized around three main points: (1) the re-examination of terms related to all perspectives of beliefs and perceptions of teachers in general and teachers of English in particular; (2) the current state of English language teaching in Vietnamese secondary schools; and (3) the importance of studying teacher belief and teacher perceptions of teachers of English about curriculum, textbooks and teaching methodology. Keywords: Teacher beliefs, teacher perceptions, ELT, TBLT.